Novel Mutations of the Tetratricopeptide Repeat Domain 7A Gene and Phenotype/Genotype Comparison - Lien, Reyin; Lin, Yung-Feng; Lai, Min-Wei; Weng, Hui-Ying; Wu, Ren-Chin; Jaing, Tang-Her; Huang, Jing-Long; Tsai, Shih-Feng; Lee, Wen-I (Frontiers in Immunology, 2017)
The gastrointestinal tract contains the largest lymphoid organ to react with pathogenic micro-organisms and suppress excess inflammation. Patients with primary immunodeficiency diseases (PIDs) can suffer from refractory diarrhea. In this study, we present two siblings who began to suffer from refractory diarrhea with a poor response to aggressive antibiotic and immunosuppressive treatment after surgical release of neonatal intestinal obstruction. Their lymphocyte proliferation was low but superoxide production and IL-10 signaling were normal. Candidate genetic approach targeted to genes involved in PIDs with inflammatory bowel disease (IBD)-like manifestation was unrevealing. Whole exome sequencing revealed novel heterozygous mutations Glu75Lys and nucleotide 520-521 CT deletion in the TTC7A gene. A Medline search identified 49 patients with TTC7A mutations, of whom 20 survived. Their phenotypes included both multiple intestinal atresia (MIA) and combined T and/or B immunodeficiency (CID) in 16, both IBD and CID in 14, isolated MIA in eight, MIA, IBD and CID complex in eight, and isolated IBD in three. Of these 98 mutant alleles over-through the coding region clustering on exon 2 (40 alleles), exon 7 (12 alleles), and exon 20 (10 alleles), two common hot-spot mutations were c.211 G>A (p.E71K in exon 2) in 26 alleles and AAGT deletion in exon 7 (+3) in 10 alleles. Kaplan-Meier analysis showed that those with bi-allelic missense mutations (p=0.0168), unaffected tetratricopeptide repeat domains (p=0.0311), and developing autoimmune disorders (p=0.001) had a relatively better prognosis. Hematopoietic stem cell transplantation (HSCT) restored immunity and seemed to decrease the frequency of infections, however refractory diarrhea persisted. Clinical improvement was reported upon intestinal and liver transplantation in a child with CID and multiple intestinal atresia of unknown genetic etiology. In conclusion, patients with TTC7A mutations presenting with the very early onset of refractory diarrhea had limit improvement by HSCT or/and tailored immunosuppressive therapy in the absence of suitable intestine donors. We suggest that MIA-CID-IBD disorder caused by TTC7A mutations should also be included in the PID classification of “immunodeficiencies affecting cellular and humoral immunity” to allow for prompt recognition and optimal treatment.